A double-layer PLGA/CoI-MeHA tissue engineering scaffold for urethral reconstruction - Chang, Mingyang; Tan, Qinyuan; Bian, Ge; Zhang, Ming; Lv, Jianing; Su, Junjie; Wang, Xiaoqing (Frontiers in Pharmacology, 2025)
IntroductionUrethral injury caused by various reasons usually leads to urethral stricture. And severe urethral stricture can further induce complications such as bladder stones, fistulas, sepsis, and even renal failure. At present, surgical methods such as urethral reconstruction and end-to-end anastomosis are commonly used to solve this problem. But this treatment method often has a high recurrence rate. So simply relying on the repair of surrounding autologous tissue cells to reconstruct the urethra is difficult to achieve long-term stability, and constructing a suitable urethral graft is an effective and feasible solution.MethodsHere, we designed and prepared a double-layer PLGA/CoI-MeHA tissue engineering scaffold to better simulate the natural anatomy of the urethra and achieve urethral tissue regeneration and reconstruction in patients with urethral stricture and Hypospadias caused by various reasons. The double-layer tissue engineering scaffold was generated using electrospinning and light curing technology.ResultsThrough electrospinning and light curing technology, we successfully screened the PLGA/CoI (7:3) electrospun membrane and MeHA (40.72%) hydrogel. Furthermore, we successfully prepared PLGA/CoI-MeHA bilayer urethral stents loaded with rabbit urethral smooth muscle cells and rabbit urethral epithelial cells, respectively, and achieved favorable results for urethral defect repair and urethral reconstruction in rabbits. The mechanical characterization of the scaffold indicates that it has sufficient mechanical strength to meet experimental and clinical needs. In addition, it showed satisfactory biocompatibility in cell experiments and in the in vitro degradation experiments. The double-layer urethral stents demonstrated exceptional performance in repairing urethral defects in rabbits.DiscussionWe had successfully designed and prepared a double-layer PLGA/CoI-MeHA tissue engineering scaffold. The stent displayed sufficient mechanical strength, good biocompatibility and degradation characteristics, and effectively simulated the natural anatomy of urethra, achieving satisfactory urethral defect reconstruction results.